TRANSFORMASI SISTEM PENDIDIKAN MADRASAH DALAM WACANA METAVERSE PADA PROGRAM KEMENAG RI - Pratiwi Amalia Putri (UIN ANTASARI BANJARMASIN, 2022)
Abstract: Metaverse is a 3D virtual space that is the result of innovation from technological sophistication in the 4.0 era. Departing from the metaverse and the conditions of the Covid-19 pandemic, Kemenag Indonesia was inspired to create a learning platform that invets in the metaverse as a transformation of the Madrasah education system in the future. This paper aims to describe how the transformation of the Madrasah education system into metaverse discourse in the future, what are the challenges, and what are the fundamental factors that make the presence of metaverse discourse in Madrasah education. This study uses a qualitative approach with a descriptive metheod. The data collection method in this study is using library research, the data such as books, articles from scientific journals, and other library data. In addiction, this study contains other secondary data originating from video on the GTK Madrasah Berbagi channel on Youtube. Data acquisition was carried out with the stages of data reduction, data presentation, and drawing conclusions. Then, the results obtained in this study is MadrasahLand as a platform for innovation results in the metaverse created by Kemenag Indonesia as a discourse in the transformation of the education system in the Madarasah environment in the future. The hope is that it can be used as an effective learning innovation, even though it is virtual but still provides the essence of reality through avatars. However, there are still several challenges that are obstacles in its development, that is (1) the lack of understanding and skills of teachers in the AR-VR field, (2) the lack of computer equipment resources for development, (3) limitations in ownership of adequate VR devices, and (4) the limitations of the internet network (4G, 5G) in its distribution in each area.Keywords: Transformation; Education; Metaverse AbstrakMetaverse adalah ruang virtual 3D yang merupakan hasil inovasi dari kecanggihan teknologi dalam era 4.0. Berangkat dari metaverse dan kondisi pandemi Covid-19, Kemenag Indonesia terinspirasi untuk menciptakan sebuah platform ruang belajar yang diinvestasikan ke dalam metaverse sebagai transformasi sistem pendidikan Madrasah di masa depan. Adapun tulisan ini bertujuan untuk mendeskripsikan tentang bagaimana transformasi sistem pendidikan Madrasah dalam wacana metaverse di masa depan, apa saja tantangannya, dan apa yang menjadi faktor mendasar yang membuat hadirnya wacana metaverse di pendidikan Madrasah. Kajian ini menggunakan upaya pendekatan kualitatif dengan metode deskriptif. Adapun metode pengumpulan data pada kajian ini adalah menggunakan library research, yaitu data-data yang berasal dari literatur kepustakaan, seperti buku, artikel dari jurnal ilmiah, serta data kepustakaan lainnya. Selain itu, kajian ini terdapat data sekunder lain yang berasal dari video pada channel GTK Madrasah Berbagi di Youtube. Perolehan data dilakukan dengan tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Kemudian, hasil yang diperoleh dalam kajian ini adalah MadrasahLand sebagai platform hasil inovasi dalam metaverse yang diciptakan oleh Kemenag Indonesia sebagai wacana dalam transformasi sistem pendidikan di lingkungan Madrasah di masa depan. Harapannya dapat dijadikan sebagai inovasi pembelajaran yang efektif, meski virtual namun tetap memberikan esensi kehadiran secara realitas melalui avatar. Namun, masih terdapat beberapa tantangan yang menjadi hambatan dalam pengembangannya, yaitu (1) masih minimnya pemahaman dan skill guru dalam bidang AR-VR, (2) masih minimnya sumber daya perangkat komputer untuk pengembangan, (3) keterbatasan dalam kepemilikan perangkat VR yang memadai, dan (4) keterbatasan jaringan internet (4G, 5G) dalam pemerataannya di setiap daerah.Kata Kunci: Transformasi; Pendidikan; Metaverse